Great society : a new history - Shlaes, Amity (Harper, an imprint of HarperCollinsPublishers, 2019)
Shlaes offers a companion to her history of the 1930s, The Forgotten Man, and shows that in fact there was scant difference between two presidents we consider opposites: Johnson and Nixon. At once history and biography, Great Society sketches moving portraits of the characters in this transformative period, from U.S. Presidents to the visionary UAW leader Walter Reuther, the founders of Intel, and Federal Reserve chairmen William McChesney Martin and Arthur Burns. Great Society casts new light on other figures too, from Ronald Reagan, then governor of California, to the socialist Michael Harrington and the protest movement leader Tom Hayden.